Development of pre-professional practice in the non-classroom context: experiences in early childhood education - Gallardo Ramírez, Jessica Natalí (2021)
The research systematized the development of pedagogical practice in the initial education career, during the first stage of the Covid-19 pandemic. For this purpose, a qualitative study was carried out, aligned to a design for the systematization of experiences method; reflecting on the evolution of the corresponding subject, with the participation of 23 students, each in charge of 20 children and their families (n = 460), with the guidance of the university professor. The results were; application of didactic-pedagogical strategies of the processes in the remote context; use of enhanced digital resources creating contextualized materials for interaction and; the approach to the unavoidable emotional accompaniment in the face of childhood vulnerability. At the end of the study, it is concluded that it is impossible to unlink educational technology from affective aspects, which were well assumed, translating into learning achievement, collective efforts in consensual work of schools, families and universities.